IMPLEMENTASI TEORI BELAJAR HUMANISTIK DALAM PENDEKATAN OPEN ENDED PADA PEMBELAJARAN MATEMATIKA - Maifit Hendriani; Neviyarni. S (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The results of the PISA test which measures students' Mathematics skills place Indonesian students in the bottom 5th position, 73rd out of 79 participating countries with an achievement score of 379 which is certainly below the OECD average of 489. Students still think of Mathematics as a subject lesson that are quite difficult. This assumption arises due to experiences that have been obtained before in the process of learning mathematics which is less fun for students. The learning process is largely determined by the learning theory mastered by educators. As a professional, educators must have knowledge of various ways so that learning objectives can be achieved. The basic knowledge that must be possessed is related to learning theory. One of the learning theories that educators can use is the humanistic learning theory. The purpose of this study is to describe the implementation of humanistic learning theory in an open-ended approach to the mathematics learning process in elementary schools. Using the library research method, it was found that open ended research utilizes humanistic learning theory in its development, which is illustrated in the four steps of the open-ended approach